Longitudinal trends in U.S. shortages of sterile solutions, 2001–17. (1st December 2018) - Mazer-Amirshahi, Maryann; Fox, Erin R.; Zocchi, Mark S.; Pines, Jesse M.; van den Anker, John N.
Abstract: Purpose: Trends in the shortages of sterile solutions in the United States were evaluated. Methods: A retrospective review of shortage data from the University of Utah Drug Information Service (UUDIS) was performed. Shortages of sterile solutions, including saline, dextrose, lactated Ringer's, and sterile water for injection, were identified. We extracted the product name, reason for the shortage, shortage duration, and primary use of the solution, examining trends in shortages over time. Results: There were 37 sterile solution shortages in the UUDIS data set, 22 of which had been resolved. The mean ± S.D. duration of a resolved shortage was 13.9 ± 9.6 months. The most common category of solution shortage was for saline products ( n = 11). Manufacturing delay was the most common reason given for shortages ( n = 19). In 2017, 12 new shortages were reported, and 15 solutions remained in shortage by year's end. This was the highest number of shortages at any time during the study period. The longest active shortage was for 5% dextrose/0.45% sodium chloride, which began in October 2007 and has yet to be resolved. Conclusion: There were 37 shortages of sterile solutions from 2001 through 2017. Shortages became more severe after Hurricane Maria damaged manufacturing facilities in Puerto Rico, with 12 new shortages reported in 2017.